Math
posted by Untamed on .
2x(x+3) = 0
Is there a way to solve that using the below methods?
Substitute zero for f(x) and find the roots of the resulting equation, or graph the function and determine the xintercepts of the graph.
Finding the roots of a single variable equation may involve factoring. Except in the case of a linear equation, set the equation to zero before factoring. Recall the following techniques for factoring: common factors, difference of two squares, trinomials in the form x^2+bx+c=0, and trinomials of the form ax^2+bx+c=0

2x(x+3)=0 then
either 2x=0 or x+3=0 so
x=0; or 3 
Thank you so much bobpursley, I was so confused on how to do this, you are a lifesaver!